(3OjhGf GdfGHZI GdPHjGfjs - (3GdfGHZg GdPHjGfj , RjGO Hf eYGhjg Hf VHGH GdPHjGfj GdZWaGfj GdeVQj, CHh GeGegs
(3ChdgG (B:s
(3bGd GdfGHZI(B: (3jGOGQ ejI HGdYdjGA aGdSfO CbhJ hWGd YdjgG SGda GdCeO s
(3BNQgG (B:s
(3hCfJ GdZjK jfaY eG jdjg hCfJ GdSe NGdWg? Je OjhGf GdfGHZI GdPHjGfj s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3hgfGc TQM dHYV GdCdaGX Hjf GdSWhQs
(3hQO CjVkG JMJ Qbe (B502(3, (B503(3, (B1303(3, (B1304(3, (B1866(3, (B1867 s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B92 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B188s
Keywords: (3GdCOHs